2019
DOI: 10.1002/jlb.ma1218-477rr
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene-B4 modulates macrophage metabolism and fat loss in type 1 diabetic mice

Abstract: Serum levels of leukotriene‐B4 (LTB4) are increased in type 1 diabetes (T1D) and it mediates systemic inflammation and macrophage reprogramming associated with this condition. Herein, we investigated the involvement of LTB4 in adiposity loss, hyperlipidemia, and changes in macrophage metabolism in a mouse model of streptozotocin‐induced T1D. LTB4 receptor (BLT1) antagonist u75302 was employed to block LTB4 effects. As expected, hypoinsulinemia in T1D was associated with hyperglycemia, low levels of glucagon, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
(81 reference statements)
0
4
0
2
Order By: Relevance
“…LTB4 increased in type 1 diabetes and mediated the systemic inflammation and macrophage reprogramming. LTB4/LTB4 receptor (BLT1) can induce fat loss and increased macrophage lipid uptake (57). LTB4 is metabolized into 20-hydroxy-leukotriene B4 and 20-carboxyl-leukotriene B4 in leukocytes and hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…LTB4 increased in type 1 diabetes and mediated the systemic inflammation and macrophage reprogramming. LTB4/LTB4 receptor (BLT1) can induce fat loss and increased macrophage lipid uptake (57). LTB4 is metabolized into 20-hydroxy-leukotriene B4 and 20-carboxyl-leukotriene B4 in leukocytes and hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…PGE2 initiated the transcription of genes that regulate the malate‐aspartate shuttle, including Got1. Another PUFA, Leukotriene‐B4 (LTB4) has also recently been linked to regulating macrophage metabolism [ 93 ]. Type 1 diabetic mice have increased levels of circulating LTB4.…”
Section: Role Of Exogenous Fatty Acids On Myeloid Cell Functionmentioning
confidence: 99%
“…20,21 Recent research showed that macrophages with enhanced glycolysis could develop into pro-inflammatory phenotype more easily in mice with hyperglycemia. 22 Therefore, whether CD226 molecules affects the glycolysis of macrophages has become a key point in our study.…”
Section: Introductionmentioning
confidence: 99%